HALITOSIS ACTIVITY AGAINST VSC METHYL MERCAPTAN COMPONENT FROM BURAHOL (Stelechocarpus burahol) FRUIT EXTRACT - Amin, Asni; Radji, Maksum; Mun'im, Abdul; Rahardjo, Anton; HERMAN SURYADI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This research was conducted to prove the activity of Stelechocarpus burahol fruit (SBF) extracts against volatile sulfur compound (VSC) of methyl mercaptan in anaerobic Gram-negative oral bacteria causing halitosis. Materials and Methods: Burahol fruits were extracted by ethanol and partitioned by several solvents and then identified the chemical constituents of the extracts using phytochemical screening test and polyphenol content by spectroscopic ultraviolet instrument. The halitosis activity against VSC of methyl mercaptan component derived from anaerobic Gram-negative oral bacteria after administration of SBF extracts with a dose of 20 mg/ml was conducted in vitro using gas chromatography-oral chroma. Results: All extracts (ethanol, ethyl acetate, butanol, water, and methanol) contain flavonoids and polyphenols, whereas saponin was found in all extracts except methanol. Halitosis activity shows the ethanol extract of SBF, has absorption capability against methyl mercaptan, and was higher than the other extracts, with catechins as control. Conclusion: All extracts of SBF (ethanol, ethyl acetate, butanol, water, and methanol) can inhibit and reduce VSC of methyl mercaptan causing halitosis. Keywords: Stelechocarpus burahol, Methyl mercaptan, Halitosis.